1988
DOI: 10.1111/j.1600-0897.1988.tb00185.x
|View full text |Cite
|
Sign up to set email alerts
|

T and B Lymphocyte Populations in Uterus Draining Lymph Nodes at Estrus and Diestrus in Wistar Rats

Abstract: In this paper, data are presented on the characterization of uterus draining lymph nodes (UDLN) B and T lymphocytes of virgin rats at estrus (E) and diestrus (D). We established that the T/B lymphocyte relationship in the UDLN is less than one at estrus and more than one at diestrus. This is due to a decrease in the percentage and in the total number of mature T cell population in association with a decrease in the percentage of the OX8 subset in the UDLN at estrus. This situation may be related to an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Other studies have shown that sex hormones can also modulate lymphocyte function at sites different from the female genital tract. Diminished graft versus host capacity of donor uterine draining lymph node cells was observed at estrus (Bonaparte et al 1986) and was associated with a decrease in the percentage and absolute number of CD8 cells (Colombo et al 1988). Moreover, studies performed in humans using peripheral blood mononuclear cells indicated that the secretion of TNF-a and IL-4 was directly correlated with the levels of estrogens in pre menopausal women (Schwarz et al 2000, Verthelyi andKlinman 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that sex hormones can also modulate lymphocyte function at sites different from the female genital tract. Diminished graft versus host capacity of donor uterine draining lymph node cells was observed at estrus (Bonaparte et al 1986) and was associated with a decrease in the percentage and absolute number of CD8 cells (Colombo et al 1988). Moreover, studies performed in humans using peripheral blood mononuclear cells indicated that the secretion of TNF-a and IL-4 was directly correlated with the levels of estrogens in pre menopausal women (Schwarz et al 2000, Verthelyi andKlinman 2000).…”
Section: Discussionmentioning
confidence: 99%